The evolution of Predictive Adaptive Responses in human life history - Nettle,Daniel; Frankenhuis,Willem E; Rickard,Ian J (PeerJ PrePrints, 2013)
Many studies have shown that adverse experience in early life is associated with accelerated reproductive timing in humans. There are two different classes of adaptive explanation for such associations. Both can be seen as predictive adaptive responses (PARs). According to external PAR hypotheses, early-life adversity provides a ‘weather forecast’ of the environmental conditions into which the individual will mature, and it is adaptive for the individual to develop an appropriate phenotype for this anticipated environment. In internal PAR hypotheses, early-life adversity has a lasting negative impact on the individual’s somatic state, such that her health is likely to fail more rapidly as she gets older, and there is an advantage to adjusting her reproductive schedule accordingly. We use a model of fluctuating environments to derive evolveability conditions for acceleration of reproductive timing in response to early-life adversity. For acceleration to evolve via the external PAR process, early-life cues must have a high degree of validity and the level of annual autocorrelation in the individual’s environment must be almost perfect. For acceleration to evolve via the internal PAR process requires that early-life experience must determine a significant fraction of the variance in survival prospects in adulthood. The two processes are not mutually exclusive, and mechanisms for calibrating reproductive timing on the basis of early experience could evolve through a combination of the predictive value of early-life adversity for the later environment and its negative impact on somatic state.
Keywords: early-life stress; life history; humans; predictive adaptive response; developmental plasticity